T120. Effects of bihemispheric tDCS combined with radial nerve stimulation in acute stroke patients. (May 2018) - Yagüe, Sara; de las Heras, Misericordia Veciana; Pedro, Jordi; Martínez-Yélamos, Antonio; Cardona, Pere; Quesada, Helena; Lara, Blanca; Kumru, Hatice; García, Belia; Montero, Jordi; Valls-Solé, Josep
Abstract : Introduction: Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that can change the excitability of the central nervous system and contribute to motor recovery of patients with stroke. The functional benefit may increase with the combination of tDCS with manoeuvres facilitating motor output. Most previous studies included patients in the chronic phase. We have evaluated the effects of tDCS coupled with radial nerve stimulation in the acute phase after stroke, as an add-on treatment to neurorehabilitation therapy that could potentially enhance motor recovery. Methods: Twenty patients with a history of first acute cortical and/or subcortical stroke (11 ischemic and 9 hemorrhagic) were included in a prospective, double-blind, randomized study. Patients presented a moderate to severe motor deficit at onset (NIHSS: 14 ± 4.4 range 6–21 and upper limb Fugl-Meyer score: 17.4 ± 15.3, range 4–60). We studied the effects of combined peripheral radial nerve stimulation (PNS) to the paretic hand and anodal tDCS to the affected hemisphere (cathodal in the contralateral hemisphere). tDCS together with PNS were applied to 11 patients: 20 min during 5 consecutive days starting 7–15 days after the stroke. The results were compared with those of 9 patients receiving PNS with sham tDCS. All patients were under routine neurorehabilitation therapy. In sessions before, immediately after and 3, 6 months and one year after tDCS, we assessed Fugl-Meyer (FM) and modified Ashworth scales (MAS), resting motor threshold (RMT), MEPs and SEPs amplitudes, contralateral and ipsilateral silent period (cSP and iSP) duration and Hmax/Mmax ratio. Results: There were significant time-related changes in clinical and neurophysiological scores, suggesting improvement in the clinically affected side in both groups (sham and real tDCS). However, there were no significant differences between real and sham tDCS in RMT, MEP amplitude, Hmax/Max ratio, cSP to TMS to the affected hemisphere, iSP to TMS to the unaffected hemisphere and FM and MAS scores ( p  < 0.05). Conclusion: Five-daily sessions bihemispheric tDCS combined with radial nerve stimulation in the acute stroke patients of our study, showed a significant improvement in some clinical and neurophysiological scores, but these changes were similar to those observed in patients that received sham tDCS and PNS.